Dry-method flexible self-supporting composite positive electrode composition, preparation method thereof and application of dry-method flexible self-supporting composite positive electrode composition in lithium ion battery
By using flexible self-supporting composite positive electrode composition in the dry electrode and using additives such as ionic liquid and lithium-containing ceramic powder, the problems of limited lithium ion transmission and insufficient mechanical properties within the dry electrode are solved, and the efficient charging and discharge cycle performance and energy density of lithium-ion batteries are improved.
Patent Information
- Application Number
- CN202510021232.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The dry electrode, especially the thick electrode, has problems such as limited internal lithium ion transmission, general mechanical properties of the electrode, and prone to cracking during the cycle, which affects the charging and discharging cycle performance of the lithium-ion battery.
The dry flexible self-supporting composite positive electrode composition is adopted, including the positive electrode active material, binder, conductive agent and additive. The additive is an ionic liquid composition or a lithium-containing ceramic powder and an ionic liquid composition. Through the combination and structural design of these materials, a denser and flexible electrode structure is formed to improve the transmission efficiency of lithium ions and the mechanical properties of the electrode.
It significantly improves the charging and discharging cycle performance of lithium-ion batteries, avoids cracking of electrodes during circulation, and improves the energy density of the battery.
Smart Images

Figure CN119852360A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries, and in particular relates to a dry-process flexible self-supporting composite positive electrode composition and a preparation method thereof and application in lithium-ion batteries. Background Art
[0002] Since their commercialization, lithium-ion batteries have accelerated the transition from oil / gas-powered vehicles to pure electric vehicles, as well as the advent of a new era of smart grids and energy intelligence. However, the energy density of lithium-ion batteries still needs to continue to increase, and the cost and pollution of the manufacturing process need to be reduced.
[0003] For the positive electrode of lithium-ion batteries, since the traditional wet coating technology uses a solvent drying method, there are disadvantages such as energy waste, high cost and pollution, electrode stratification, and limited electrode thickness. In this context, dry film manufacturing technology that does not use any solvents is considered to be a good solution to the above problems. Compared with traditional wet electrodes, dry electrodes have incomparable energy density and are regarded as competitive candidates. However, dry electrodes, especially thick electrodes, have limited internal lithium ion transport, general electrode mechanical properties, and are prone to cracking during the cycle, which greatly affects the charge and discharge cycle performance of lithium-ion batteries. Summary of the invention
[0004] In view of this, the object of the present invention is to provide a dry-process flexible self-supporting composite positive electrode composition and a preparation method thereof and application in a lithium-ion battery. The lithium-ion battery prepared using the dry-process flexible self-supporting composite positive electrode composition has excellent charge and discharge cycle performance.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] The present invention provides a dry-process flexible self-supporting composite positive electrode composition, comprising a positive electrode active material, a binder, a conductive agent and an additive, wherein the additive comprises an ionic liquid composition, or a lithium-containing ceramic powder and an ionic liquid composition;
[0007] The ionic liquid composition comprises an ionic liquid and a lithium salt component, wherein the lithium salt component comprises a lithium salt, or a lithium salt and succinonitrile.
[0008] Preferably, the lithium-containing ceramic powder includes one or more of lithium aluminum titanium phosphate powder, lithium lanthanum zirconium oxide powder, lanthanum titanate lithium powder, lithium aluminate powder, doped lithium lanthanum zirconium oxide powder, lithium germanium phosphorus sulfur powder and lithium phosphorus sulfur powder.
[0009] Preferably, the mass ratio of succinonitrile, ionic liquid and lithium salt is (0-60):(5-70):(1-40).
[0010] Preferably, the ionic liquid includes an imidazole ionic liquid and / or a pyrrolidine ionic liquid.
[0011] Preferably, the imidazole ionic liquid is 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide or 1-ethyl-3-methylimidazolium tetraborate; and the pyrrolidine ionic liquid is 1-n-butyl-1-methylpyrrolidine bis(trifluoromethanesulfonyl)imide.
[0012] Preferably, the positive electrode active material includes one or more of layered lithium metal oxides, olivine structure materials, monoclinic structure compounds, flaky structure materials, spinel structure materials, polyanion structure materials and lithium-rich manganese-based solid solution materials.
[0013] The present invention also provides a method for preparing the dry flexible self-supporting composite positive electrode composition described in the above technical solution, comprising the following steps:
[0014] The positive electrode active material, the conductive agent, the additive and the binder are mixed to obtain the dry process flexible self-supporting composite positive electrode composition.
[0015] The present invention also provides the use of the dry-process flexible self-supporting composite positive electrode composition described in the above technical solution or the dry-process flexible self-supporting composite positive electrode composition prepared by the preparation method described in the above technical solution in a lithium-ion battery.
[0016] The present invention also provides a dry-process flexible self-supporting composite positive electrode, which is a fibrous membrane. The material of the dry-process flexible self-supporting composite positive electrode is the dry-process flexible self-supporting composite positive electrode composition described in the above technical scheme or the dry-process flexible self-supporting composite positive electrode composition prepared by the preparation method described in the above technical scheme.
[0017] The present invention also provides a lithium-ion battery, wherein the positive electrode of the lithium-ion battery is the dry-process flexible self-supporting composite positive electrode described in the above technical solution.
[0018] The present invention provides a dry process flexible self-supporting composite positive electrode composition, including positive electrode active material, binder, conductive agent and additive, wherein the additive includes ionic liquid composition, or lithium-containing ceramic powder and ionic liquid composition; the ionic liquid composition includes ionic liquid and lithium salt component, wherein the lithium salt component includes lithium salt, or lithium salt and succinonitrile. The present invention applies lithium-containing ceramic powder and ionic liquid to the dry process composite positive electrode, because the ceramic powder with smaller particle size can be tightly filled in the gap between the positive electrode active material particles to form a more compact and solid structure, and the ionic liquid with a certain viscosity is filled between the solid particles, so that it has good flexibility and mechanical properties, avoids cracking during the cycle process, and can also greatly improve the surface load (mass of active material per unit area) of the dry process flexible self-supporting composite positive electrode composition, thereby improving the overall energy density of the battery; at the same time, the lithium-containing ceramic powder and ionic liquid contained can interact with lithium ions and conduct lithium ions, thereby constructing a rich lithium ion transmission channel, assisting the rapid transportation of lithium ions inside the positive electrode, thereby increasing the charge and discharge cycle performance of the lithium ion battery.
[0019] The present invention also provides a method for preparing a dry-process flexible self-supporting composite positive electrode composition, which has a simple preparation process and is environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a SEM cross-sectional view of the dry-process flexible self-supporting composite positive electrode prepared in Example 1;
[0021] Figure 2 The cycle performance diagram of the liquid button cell assembled with the dry flexible self-supporting composite positive electrode prepared in Example 2 at a rate of 0.1C;
[0022] Figure 3 The charge and discharge curve of the liquid button cell assembled with the dry flexible self-supporting composite positive electrode prepared in Example 2 at a rate of 0.1C;
[0023] Figure 4 The cycle performance diagram of the quasi-solid-state button cell assembled with the dry-process flexible self-supporting composite positive electrode prepared in Example 3 at a rate of 0.1C;
[0024] Figure 5 The charge and discharge curve of the quasi-solid-state button cell assembled with the dry-process flexible self-supporting composite positive electrode prepared in Example 3 at a rate of 0.1C;
[0025] Figure 6 The cycle performance diagram of the solid-state button battery assembled with the dry flexible self-supporting composite positive electrode prepared in Example 4 at a rate of 0.1C;
[0026] Figure 7The charge and discharge curve of the solid-state button battery assembled with the dry flexible self-supporting composite positive electrode prepared in Example 4 at a rate of 0.1C;
[0027] Figure 8 The charge and discharge curve of the NMC622 / lithium metal battery assembled with conventional dry electrodes in Comparative Example 1 at a rate of 0.1C;
[0028] Fig. 9 This is a diagram of the flexibility and mechanical properties of the dry-process flexible self-supporting composite positive electrode composition prepared in Example 2. DETAILED DESCRIPTION
[0029] The present invention provides a dry-process flexible self-supporting composite positive electrode composition, comprising a positive electrode active material, a binder, a conductive agent and an additive, wherein the additive comprises an ionic liquid composition, or a lithium-containing ceramic powder and an ionic liquid composition;
[0030] The ionic liquid composition comprises an ionic liquid and a lithium salt component, wherein the lithium salt component comprises a lithium salt, or a lithium salt and succinonitrile.
[0031] Unless otherwise specified, the present invention has no special requirements on the sources of the raw materials used, and commercially available products known to those skilled in the art may be used.
[0032] The dry-process flexible self-supporting composite positive electrode composition provided by the present invention comprises a positive electrode active material.
[0033] As an embodiment, the positive electrode active material includes one or more of layered lithium metal oxide, olivine structure material, monoclinic structure compound, flaky structure material, spinel structure material, polyanion structure material and lithium-rich manganese-based solid solution material, and in a specific embodiment, it is layered lithium metal oxide.
[0034] As an embodiment, the layered lithium metal oxide includes one or more of lithium cobalt oxide (LiCoO2), layered lithium manganese oxide (LiMn2O4), lithium nickel oxide (LiNiO2), lithium nickel cobalt manganese oxide (NMC) and lithium nickel cobalt aluminum oxide (NCA), and in a specific embodiment, it is lithium nickel cobalt manganese oxide (NMC); the lithium nickel cobalt manganese oxide is LiNi6Mn2Co2O2, NCM622. The layered lithium metal oxide has both higher capacity and better cycle stability.
[0035] As an embodiment, the lithium nickel cobalt manganese oxide is LiNi x Mn y Co z O2, x+y+z=1, x≥0.6; the lithium nickel cobalt aluminum oxide is LiNi 0.8 Co 0.15 Al 0.05 O2,
[0036] As an embodiment, the olivine structural material includes lithium manganese iron phosphate (LMFP); the lithium manganese iron phosphate is LiMn x Fe 1-x PO4,0<x<1.
[0037] As an embodiment, the monoclinic compound is lithium vanadium phosphate (Li3V2(PO4)3).
[0038] As an embodiment, the sheet structure material is lithium vanadium phosphate (LiVOPO4)
[0039] As an embodiment, the spinel structure material is lithium manganate (LiMn2O4) and / or lithium titanate (Li2TiO3).
[0040] As an embodiment, the polyanion structural material includes one or more of lithium iron phosphate (LiFePO4), lithium cobalt phosphate (LiCoPO4) and lithium iron silicate (Li2FeSiO4), and in a specific embodiment, it is lithium iron phosphate (LiFePO4).
[0041] As an embodiment, the lithium-rich manganese-based solid solution material is xLi2MnO3(1-x)LiMn y M 1-y O2, M = Ni or Co, x = 0 ~ 1, y = 0 ~ 1, in the specific embodiment 0.3Li2MnO30.7LiMn 0.5 Ni 0.5 O2.
[0042] When the positive electrode active materials are of the above types, the present invention has no special limitation on the ratio of different types of positive electrode active materials, and any ratio may be used.
[0043] The dry-process flexible self-supporting composite positive electrode composition provided by the present invention comprises a binder.
[0044] As an embodiment, the binder is polytetrafluoroethylene binder (PTFE). Increasing the binder content will improve the mechanical properties and flexibility, but too much will affect the cycle performance of the battery.
[0045] The dry-process flexible self-supporting composite positive electrode composition provided by the present invention comprises a conductive agent.
[0046] As an embodiment, the conductive agent is a carbon material; the carbon material includes one or more of conductive carbon black, conductive graphite, superconducting carbon, carbon dots, carbon fibers, carbon nanotubes and graphene, and in a specific embodiment, it is conductive carbon black or carbon nanotubes.
[0047] As an implementation manner, the conductive carbon black includes acetylene black, Super-P, Ketjen black, and in the specific embodiment, Super-P.
[0048] As an embodiment, the conductive graphite includes KS-6 and / or KS-15, and in a specific embodiment, it is KS-6.
[0049] As an embodiment, the mass ratio of the positive electrode active material, the binder and the conductive agent is (40-80):(1-5):(5-20), and in a specific embodiment it is (40-70):(1-5):(5-20).
[0050] Different conductive agents have different effects on the internal resistance of the battery. Usually, two or three conductive agents are used in the battery design process to achieve the best conductive effect and form the best conductive network. As the content of conductive agent increases, the electron conductivity of the positive electrode increases, which is beneficial to improving the cycle performance, but adding too much will reduce the energy density of the positive electrode.
[0051] The dry-process flexible self-supporting composite positive electrode composition provided by the present invention comprises additives.
[0052] As an embodiment, the additive includes an ionic liquid composition, or a lithium-containing ceramic powder and an ionic liquid composition.
[0053] As an embodiment, the lithium-containing ceramic powder includes one or more of lithium aluminum titanium phosphate (LATP) powder, lithium lanthanum zirconium oxide (LLZO) powder, lithium lanthanum titanate (LLTO) powder, lithium aluminate (LAO) powder, doped lithium lanthanum zirconium oxide (LLZMO) powder, lithium germanium phosphorus sulfur (LGPS) powder and lithium phosphorus sulfur (LPS) powder, and in a specific embodiment, it is lithium aluminum titanium phosphate powder or lithium lanthanum zirconium oxide powder.
[0054] As an embodiment, the structural formula of the lithium aluminum titanium phosphate (LATP) powder is Li 1+x Al x Ti 2-x (PO4)3, 0<x≤0.5, in the specific embodiment, Li 1.5 Al 0.5 Ti 1.5 (PO4)3; the structural formula of the lithium lanthanum zirconium oxide (LLZO) powder is Li7La3Zr2O 12 The structural formula of the lanthanum lithium titanate (LLTO) powder is Li y La 2 / 3-y TiO3, 0.04<y≤0.16, in the specific embodiment, Li 0.1 La 0.5667 TiO3; the structural formula of the lithium aluminate powder is LiAlO2 (LAO); the structural formula of the doped lithium lanthanum zirconium oxide (LLZMO) powder is Li7-z Ln3Z 2-z M z O 12 , M=Ta or Nb, 0.25<z<2, in the specific embodiment, it is Li6La3ZrTa2O 12 or Li6La3ZrNb2O 12 The structural formula of the lithium germanium phosphorus sulfur (LGPS) powder is Li 7+a Ge a P 3-a S 11 , 0.5<a<3, in the specific embodiment, Li8Ge1P2S 11 ; The structural formula of the lithium phosphorus sulfur (LPS) powder is bLi2S·(100-b)P2S5, 25<b<75, and in the specific embodiment it is 50Li2S·50P2S5.
[0055] Different ceramic powders have slight effects on mechanical and electrochemical properties due to different ionic conductivity and microstructure, but the overall difference is not significant.
[0056] As an embodiment, the mass ratio of the positive electrode active material to the ionic liquid composition is (40-80):(20-50), and in a specific embodiment, it is (40-70):(20-40).
[0057] As an embodiment, the ionic liquid composition includes an ionic liquid and a lithium salt component, and the lithium salt component includes a lithium salt, or a lithium salt and succinonitrile.
[0058] Succinonitrile can form a deep eutectic solvent with lithium salts and ionic liquids, which can reduce the viscosity of the mixed liquid, increase the ionic conductivity, and improve the cycle performance of the composite positive electrode at high current density. At the same time, the carbon and nitrogen in succinonitrile have very high bond energy, which can improve the oxidation stability of the ionic liquid mixture, thereby improving the cycle stability of the composite positive electrode at high voltage.
[0059] As an embodiment, the ionic liquid includes an imidazole ionic liquid and / or a pyrrolidine ionic liquid; the imidazole ionic liquid is 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide (EMIM-TFSI) or 1-ethyl-3-methylimidazolium tetraborate (EMIM-BF4), and in a specific embodiment it is 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide (EMIM-TFSI); the pyrrolidine ionic liquid is 1-n-butyl-1-methylpyrrolidine bis(trifluoromethanesulfonyl)imide (Pyr14-TFSI).
[0060] For the two types of ionic liquids, imidazolium ionic liquids have lower viscosity and higher ionic conductivity, which can better promote the transmission of lithium ions and improve the cycle performance of the positive electrode under high current density; pyrrolidine ionic liquids have a higher electrochemical window and can adapt to higher voltage positive electrodes.
[0061] As an embodiment, the lithium salt includes one or more of lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium hexafluorophosphate (LiPF6), lithium bis(trifluoromethanesulfonyl imide) (LiTFSI), lithium tetrafluoroborate (LiBF4), lithium trifluoromethanesulfonate (LiCF3SO3) and lithium bis(trifluoromethanesulfonyl imide) (LiBOB), and in a specific embodiment, lithium bis(trifluoromethanesulfonyl imide) is used. When the lithium salt is the above-mentioned lithium salt, the present invention has no special limitation on the ratio of different types of lithium salts, and any ratio can be used.
[0062] As an embodiment, the mass ratio of succinonitrile, ionic liquid and lithium salt is (0-60):(5-70):(1-40), as another embodiment it is (0-10):(5-30):(2-30), and in a specific embodiment it is 50:40:10.
[0063] As an embodiment, the preparation method of the ionic liquid composition is: mixing the ionic liquid, lithium salt and succinonitrile and stirring to obtain the ionic liquid composition; the stirring temperature is 30 to 80°C, and in a specific embodiment, it is 30 to 50°C; the stirring time is 1 to 12 hours, and in a specific embodiment, it is 6 to 12 hours. The present invention has no special limitation on the stirring rate, and the stirring rate well known in the art can be used to mix the materials uniformly.
[0064] As an embodiment, the mass ratio of the lithium-containing ceramic powder to the ionic liquid composition is (0-20):(20-50), and in a specific embodiment, it is (1-10):(20-40).
[0065] The dry-process flexible self-supporting composite positive electrode composition provided by the present invention has extremely high active loading and excellent flexibility, which can greatly improve the energy density of the battery. In addition, the dry-process flexible self-supporting composite positive electrode composition structure contains ionic liquid, lithium salt and lithium-containing ceramic powder, which can provide a rich lithium-conducting network, improve the lithium ion transmission efficiency inside the thick positive electrode, and also give the electrode material better flexibility and mechanical properties, avoid cracking during the cycle process, and improve the charge and discharge cycle performance of the lithium-ion battery.
[0066] The present invention also provides a method for preparing the dry flexible self-supporting composite positive electrode composition described in the above technical solution, comprising the following steps:
[0067] The positive electrode active material, the conductive agent, the additive and the binder are mixed to obtain the dry process flexible self-supporting composite positive electrode composition.
[0068] The present invention has no special limitation on the mixing process, and any mixing method known in the art may be used.
[0069] The present invention also provides the use of the dry-process flexible self-supporting composite positive electrode composition described in the above technical solution or the dry-process flexible self-supporting composite positive electrode composition prepared by the preparation method described in the above technical solution in a lithium-ion battery.
[0070] The present invention also provides a dry-process flexible self-supporting composite positive electrode, which is a fibrous membrane. The material of the dry-process flexible self-supporting composite positive electrode is the dry-process flexible self-supporting composite positive electrode composition described in the above technical scheme or the dry-process flexible self-supporting composite positive electrode composition prepared by the preparation method described in the above technical scheme.
[0071] As an embodiment, the preparation method of the dry-process flexible self-supporting composite positive electrode comprises the following steps: subjecting the dry-process flexible self-supporting composite positive electrode composition to a fiberization treatment and a heat calendering treatment in sequence to obtain the dry-process flexible self-supporting composite positive electrode.
[0072] As an embodiment, the fiberization treatment includes at least one of air flow milling, grinding, shearing and extrusion, and in a specific embodiment, air flow milling or grinding.
[0073] As an implementation mode, the equipment used for the air flow mill is an air flow pulverizer.
[0074] The samples processed by air jet milling are flocculent, and the samples ground manually are often flakes or blocks. The binder needs to be fully fiberized, otherwise it may result in the failure to form a film or increase the impedance of the dry flexible self-supporting composite positive electrode due to binder agglomeration.
[0075] As an implementation mode, the equipment used for extrusion is a twin-screw extruder; the equipment used for internal mixing is an internal mixer; the equipment used for shearing is a shearing machine; and the grinding is grinding with a mortar.
[0076] As an implementation mode, the rotation speed of the air flow mill is 300-650rpm, 400-500rpm in a specific embodiment, and the time is 5-20min, 10-15min in a specific embodiment; the shearing rotation speed is 20000-30000rpm, 25000rpm in a specific embodiment, and the time is 5-20min, 10-15min in a specific embodiment; the extrusion pressure is 1-2MPa, 1.5-2MPa in a specific embodiment; the extrusion times is greater than 2 times, 3 times in a specific embodiment.
[0077] In the present invention, fiberization treatment refers to that the binder material is regularly arranged in a certain direction to form fibers under the action of high shear force. The binder with a high degree of fiberization is more conducive to overlapping a more complete three-dimensional network structure, so that the binder is evenly distributed between other components of the dry flexible self-supporting composite positive electrode, thereby improving the stability of the positive electrode sheet peeling strength.
[0078] As an embodiment, the temperature of the heating and calendering treatment is 40 to 160°C, and in a specific embodiment, 60 to 120°C; the heating and calendering treatment is performed by roller pressing. Heating and calendering can increase the density of the dry-process flexible self-supporting composite positive electrode, reduce internal pores, and improve mechanical properties and cycle stability.
[0079] As an implementation mode, the thickness of the dry-process flexible self-supporting composite positive electrode is 50 to 800 μm, and in a specific embodiment, it is 100 to 300 μm.
[0080] The present invention also provides a lithium-ion battery, wherein the positive electrode of the lithium-ion battery is the dry-process flexible self-supporting composite positive electrode described in the above technical solution.
[0081] As an embodiment, the lithium-ion battery further includes a negative electrode; the negative electrode is a metal lithium sheet.
[0082] As an embodiment, the lithium-ion battery further includes an electrolyte.
[0083] As an embodiment, the electrolyte includes ethylene carbonate (EC), dimethyl carbonate (DMC) and a lithium salt; the volume ratio of the ethylene carbonate (EC) to the dimethyl carbonate (DMC) is 0.5 to 2:1, and in a specific embodiment, it is 1:1; the volume percentage of ethylene carbonate (EC) in the electrolyte is 33.3 to 66.7 vol%), and in a specific embodiment, it is 50 vol%; the volume percentage of dimethyl carbonate (DMC) in the electrolyte is 66.7 to 33.3 vol%, and in a specific embodiment, it is 50 vol%; the lithium salt is lithium bis(trifluoromethanesulfonyl imide) (LITFSI); the concentration of the lithium salt in the electrolyte is 0.5 to 2 mol / L, and in a specific embodiment, it is 1 to 1.5 mol / L.
[0084] As an embodiment, the electrolyte includes a semi-solid electrolyte or a solid electrolyte; the semi-solid electrolyte is a PICEC soft material electrolyte, and the raw materials for preparing the PICEC soft material electrolyte include succinonitrile (SN), polyethylene oxide (PEO), bis(trifluoromethanesulfonyl imide) lithium (LiTFSI) and fluoroethylene carbonate (FEC); the mass ratio of succinonitrile (SN), polyethylene oxide (PEO), bis(trifluoromethanesulfonyl imide) lithium (LiTFSI) and fluoroethylene carbonate (FEC) is 8-12:1-3:1-3:1-5, and in a specific embodiment, it is 10:1.5:1.9:2.5; the mass ratio of the polyethylene oxide is 1:1:1.5:1.9:2.5:1 ... The molecular weight is 100,000 to 1,000,000, and in a specific embodiment, it is 100,000 to 600,000; the solid electrolyte membrane includes polytetrafluoroethylene (PTFE), lithium lanthanum zirconium oxide (LLTZO), 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide (EMIM-TFSI) and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI); the mass ratio of the polytetrafluoroethylene (PTFE), lithium lanthanum zirconium oxide (LLTZO), 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide (EMIM-TFSI) and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) is 1 to 8:80 to 95:10 to 20:1 to 10, and in a specific embodiment, it is 5:95:15:5.
[0085] As an embodiment, when the lithium-ion battery includes an electrolyte or a semi-solid electrolyte, the lithium-ion battery further includes a separator; and the separator is a polyethylene (PE) separator.
[0086] The technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention, but they should not be construed as limiting the protection scope of the present invention.
[0087] Example 1
[0088] Preparation of raw materials: lithium nickel cobalt manganese oxide (LiNi6Mn2Co2O2, NCM622), polytetrafluoroethylene (PTFE), SuperP, lithium lanthanum zirconium oxide (Li7La3Zr2O 12 , LLZO), succinonitrile (SN), 1-n-butyl-1-methylpyrrolidine bis (trifluoromethanesulfonyl) imide (Pyr 14 -TFSI) and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI);
[0089] 0.02 g of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), 0.08 g of 1-n-butyl-1-methylpyrrolidine bis(trifluoromethanesulfonyl)imide (Pyr 14-TFSI), 0.1g succinonitrile (SN) were mixed at 30°C and stirred at 500rpm for 12h, the obtained ionic liquid composition was mixed with 0.20g lithium nickel cobalt manganese oxide (LiNi6Mn2Co2O2, NCM622), 0.07g SuperP, 0.005g lithium lanthanum zirconium oxide and 0.025g polytetrafluoroethylene (PTFE), and after grinding and mixing evenly in a mortar, the obtained fiber mixture was rolled at 60°C into a dry flexible self-supporting composite positive electrode composition with a thickness of 200μm.
[0090] Example 2
[0091] Preparation of raw materials: lithium nickel cobalt manganese oxide (LiNi6Mn2Co2O2, NCM622), polytetrafluoroethylene (PTFE), SuperP, lithium lanthanum zirconium oxide (Li7La3Zr2O 12 , LLZO), succinonitrile (SN), 1-n-butyl-1-methylpyrrolidine bis(trifluoromethanesulfonyl)imide (Pyr14-TFSI) and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI);
[0092] 0.01g lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), 0.04g 1-n-butyl-1-methylpyrrolidine bis(trifluoromethanesulfonyl)imide (Pyr14-TFSI), and 0.05g succinonitrile (SN) were mixed at 50°C and stirred at 400rpm for 12h. The obtained ionic liquid composition was mixed with 0.30g lithium nickel cobalt manganese oxide (LiNi6Mn2Co2O2, NCM622), 0.06g SuperP, 0.015g lithium lanthanum zirconium oxide, and 0.025g polytetrafluoroethylene (PTFE). After grinding and mixing evenly in a mortar, the obtained fiber mixture was rolled at 80°C into a dry flexible self-supporting composite positive electrode composition with a thickness of 100μm.
[0093] Example 3
[0094] Preparation of raw materials: lithium nickel cobalt manganese oxide (LiNi6Mn2Co2O2, NCM622), polytetrafluoroethylene (PTFE), SuperP, lithium lanthanum zirconium oxide (Li7La3Zr2O 12 , LLZO), 1-n-butyl-1-methylpyrrolidine bis(trifluoromethanesulfonyl)imide (Pyr14-TFSI) and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI);
[0095] 0.06 g of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and 0.14 g of 1-n-butyl-1-methylpyrrolidine bis(trifluoromethanesulfonyl)imide (Pyr14-TFSI) were mixed at 30°C and stirred at 400 rpm for 12 h. The obtained ionic liquid composition was mixed with 0.20 g of lithium nickel cobalt manganese oxide (LiNi6Mn2Co2O2, NCM622), 0.07 g of SuperP, 0.005 g of lithium lanthanum zirconium oxide and 0.025 g of polytetrafluoroethylene (PTFE). After grinding and mixing evenly in a mortar, the obtained fiber mixture was rolled at 80°C into a dry flexible self-supporting composite positive electrode composition with a thickness of 200 μm.
[0096] Example 4
[0097] Preparation of raw materials: lithium nickel cobalt manganese oxide (LiNi6Mn2Co2O2, NCM622), polytetrafluoroethylene (PTFE), carbon nanotubes (CNT), lithium lanthanum zirconium oxide (Li7La3Zr2O 12 , LLZO), succinonitrile (SN), 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide (EMIM-TFSI), and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI);
[0098] 0.01 g of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), 0.04 g of 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide (EMIM-TFSI), and 0.05 g of succinonitrile (SN) were mixed at 50°C and stirred at 400 rpm for 12 h. The obtained ionic liquid composition was mixed with 0.35 g of lithium nickel cobalt manganese oxide (LiNi6Mn2Co2O2, NCM622), 0.025 g of carbon nanotubes (CNTs), 0.015 g of lithium lanthanum zirconium oxide, and 0.01 g of polytetrafluoroethylene (PTFE). The mixture was milled using a jet mill, and the obtained fiber mixture was rolled at 120°C into a dry flexible self-supporting composite positive electrode composition with a thickness of 150 μm.
[0099] Comparative Example 1
[0100] Conventional dry electrode, preparation raw materials: lithium nickel cobalt manganese oxide (LiNi6Mn2Co2O2, NCM622), polytetrafluoroethylene (PTFE), SuperP in a mass ratio of 40:5:15;
[0101] 0.20 g of lithium nickel cobalt manganese oxide (LiNi6Mn2Co2O2, NCM622), 0.075 g of SuperP and 0.025 g of polytetrafluoroethylene (PTFE) were mixed, ground and mixed evenly using a mortar, and then the obtained fiber mixture was rolled at 60°C to form a conventional dry electrode with a thickness of 200 μm.
[0102] Comparative Example 2
[0103] The difference from Example 3 is that lithium lanthanum zirconium oxide (Li7La3Zr2O 12 , LLZO), succinonitrile (SN), 1-n-butyl-1-methylpyrrolidine bis(trifluoromethanesulfonyl)imide (Pyr14-TFSI) and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), and the rest of the contents are consistent with Example 3.
[0104] Comparative Example 3
[0105] The difference from Example 3 is that 1-n-butyl-1-methylpyrrolidine bis(trifluoromethanesulfonyl)imide (Pyr14-TFSI) is not added, and the rest of the contents are consistent with Example 3.
[0106] Performance Testing
[0107] (1) The surface of the dry-process flexible self-supporting composite positive electrode composition in Example 1 was tested by scanning electron microscopy, and the results are as follows: Figure 1 shown.
[0108] Depend on Figure 1 From the scanning electron microscope plan view, it can be seen that the solid active material (NCM622) and ionic liquid additive components (ionic liquid mixture) are evenly distributed on the surface of the dry flexible self-supporting composite positive electrode composition. This structure can effectively improve the efficiency of lithium ion transmission and enhance the battery's cycle performance.
[0109] (2) Characterization of battery performance
[0110] The dry-process flexible self-supporting composite positive electrode composition of Example 2 was cut into discs with a diameter of 10 mm, and the active mass surface density (NCM622 density) was 25 mg·cm -1 , and then assembled with PE separator, electrolyte (ethylene carbonate (EC): dimethyl carbonate (DMC) = 1:1 vol%, the lithium salt in the electrolyte is bis(trifluoromethanesulfonyl imide) lithium (LITFSI, concentration is 1 mol / L)) and metal lithium sheet into a button lithium metal battery (NMC 622 / lithium metal battery), and the charge and discharge curve and cycle performance of the button battery were tested with a NEWARE battery program-controlled tester. The cycle performance results at a rate of 0.1C are shown in FIG. Figure 2 As shown, the specific capacity-voltage curve results at 0.1C rate are as follows Figure 3 shown.
[0111] Depend on Figure 2 and Figure 3It can be seen that the NMC 622 / lithium metal battery using a dry flexible self-supporting composite positive electrode composition can reach a capacity of 150 mAh / g at room temperature and 0.1C, and its capacity retention rate is still 145 mAh / g after 60 cycles.
[0112] (3) The dry-process flexible self-supporting composite positive electrode composition of Example 3 was cut into round pieces with a diameter of 10 mm and an active mass surface density of 25 mg·cm -1 , and then assembled with PE separator, PICEC soft material electrolyte (succinonitrile (SN): polyethylene oxide (PEO molecular weight 60W): bis(trifluoromethanesulfonyl imide) lithium (LiTFSI): fluoroethylene carbonate (FEC) = 10:1.5:1.9:2.5wt.%) and metal lithium sheet into a button lithium metal battery (NMC622 / lithium metal battery), and the charge and discharge curve and cycle performance of the button battery were tested with a NEWARE battery program-controlled tester. The cycle performance results at a rate of 0.1C are shown in the figure. Figure 4 As shown, the specific capacity-voltage curve results at 0.1C rate are as follows Figure 5 shown.
[0113] Depend on Figure 4 and Figure 5 It can be seen that the capacity retention rate of the NMC622 / lithium metal battery assembled with the dry flexible self-supporting composite positive electrode composition is still 160 mAh / g after 30 cycles at room temperature and 0.1C.
[0114] (4) The dry-process flexible self-supporting composite positive electrode composition of Example 4 was cut into round pieces with a diameter of 10 mm and an active mass surface density of 15 mg·cm -1 Then, it was assembled with a solid electrolyte membrane (wherein, the solid electrolyte membrane is composed of 5wt% polytetrafluoroethylene (PTFE), 75wt% lithium lanthanum zirconium oxide (LLTZO), 15wt% 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide (EMIM-TFSI) and 5wt% lithium bis(trifluoromethanesulfonyl)imide (LiTFSI)) and a metal lithium sheet into a button-type lithium metal battery (NMC622 / lithium metal battery). The charge and discharge curve and cycle performance of the button-type battery were tested using a NEWARE battery program-controlled tester. The cycle performance results at a rate of 0.1C are shown in FIG. Figure 6 As shown, the specific capacity-voltage curve results at 0.1C rate are as follows Figure 7 shown.
[0115] Depend on Figure 6 and Figure 7 It can be seen that the capacity retention rate of the NMC622 / lithium metal battery assembled with the dry flexible self-supporting composite positive electrode composition is still 160 mAh / g after 80 cycles at room temperature and 0.1C.
[0116] (5) The charge and discharge curves of the conventional dry electrode assembled NMC622 / lithium metal battery of Comparative Example 1 at room temperature and 0.1°C were tested using a NEWARE battery program-controlled tester. Figure 8 shown.
[0117] Depend on Figure 8 It can be seen that the NMC622 / lithium metal battery assembled using conventional dry electrodes has a very low capacity at room temperature 0.1C and poor battery cycle performance.
[0118] (6) Fig. 9 This is a diagram of the flexibility and mechanical properties of the dry-process flexible self-supporting composite positive electrode composition (sample size is 30×20 mm) prepared in Example 2, where a uses a weight (50 g) to demonstrate the mechanical properties, and b~d demonstrate the flexibility.
[0119] Depend on Fig. 9 It can be seen that the dry-process flexible self-supporting composite positive electrode composition prepared in Example 2 did not undergo any deformation under the gravity of a 50g weight, and had good mechanical properties; the composite positive electrode composition could be bent and folded arbitrarily and still return to its original shape, and had good flexibility.
[0120] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention rather than all the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A dry-process flexible self-supporting composite positive electrode composition, characterized in that: It includes a positive electrode active material, a binder, a conductive agent and an additive, wherein the additive includes an ionic liquid composition, or a lithium-containing ceramic powder and an ionic liquid composition; The ionic liquid composition comprises an ionic liquid and a lithium salt component, wherein the lithium salt component comprises a lithium salt, or a lithium salt and succinonitrile.
2. The dry-process flexible self-supporting composite positive electrode composition according to claim 1, characterized in that: The lithium-containing ceramic powder includes one or more of lithium aluminum titanium phosphate powder, lithium lanthanum zirconium oxide powder, lanthanum titanate lithium powder, lithium aluminate powder, doped lithium lanthanum zirconium oxide powder, lithium germanium phosphorus sulfur powder and lithium phosphorus sulfur powder.
3. The dry-process flexible self-supporting composite positive electrode composition according to claim 1, characterized in that: The mass ratio of the succinonitrile, the ionic liquid and the lithium salt is (0-60):(5-70):(1-40).
4. The dry-process flexible self-supporting composite positive electrode composition according to claim 1 or 3, characterized in that: The ionic liquid includes an imidazole ionic liquid and / or a pyrrolidine ionic liquid.
5. The dry-process flexible self-supporting composite positive electrode composition according to claim 4, characterized in that: The imidazole ionic liquid is 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide or 1-ethyl-3-methylimidazolium tetraborate; the pyrrolidine ionic liquid is 1-n-butyl-1-methylpyrrolidine bis(trifluoromethanesulfonyl)imide.
6. The dry-process flexible self-supporting composite positive electrode composition according to claim 1, characterized in that: The positive electrode active material includes one or more of layered lithium metal oxides, olivine structure materials, monoclinic structure compounds, sheet structure materials, spinel structure materials, polyanion structure materials and lithium-rich manganese-based solid solution materials.
7. The method for preparing a dry flexible self-supporting composite positive electrode composition according to any one of claims 1 to 6, characterized in that: The following steps are involved: The positive electrode active material, the conductive agent, the additive and the binder are mixed to obtain the dry process flexible self-supporting composite positive electrode composition.
8. Use of the dry-process flexible self-supporting composite positive electrode composition according to any one of claims 1 to 6 or the dry-process flexible self-supporting composite positive electrode composition prepared by the preparation method according to claim 7 in a lithium-ion battery.
9. A dry-process flexible self-supporting composite positive electrode, characterized in that: The dry-process flexible self-supporting composite positive electrode is a fibrous membrane, and the material of the dry-process flexible self-supporting composite positive electrode is the dry-process flexible self-supporting composite positive electrode composition described in any one of claims 1 to 6 or the dry-process flexible self-supporting composite positive electrode composition prepared by the preparation method described in claim 7.
10. A lithium ion battery, characterized in that: The positive electrode of the lithium-ion battery is the dry-process flexible self-supporting composite positive electrode as claimed in claim 9.
Citation Information
Patent Citations
Preparation method of dry-method electrode pole piece, electrode pole piece and battery cell
CN113871561A
Electrode for power storage device, and power storage device
CN114270559A
Oxide solid electrolyte membrane, preparation method thereof and lithium metal battery
CN117317353A
Cited By
Preparation method of high-performance modified dry electrode and application of high-performance modified dry electrode in lithium metal battery
CN120878764A
Positive electrode sheet and preparation method therefor, solid-state battery cell, battery device, and electric device
WO2026076933A1